Socioeconomic and ecological perceptions and barriers to urban tree distribution and reforestation programs (2018)
Tree planting and reforestation initiatives in urban and peri-urban areas often use tree distribution or “giveaway” programs as a strategy to increase tree cover and subsequent benefits. However, the effectiveness of these programs in terms of increasing overall tree cover and providing benefits to low-income and disadvantaged communities has been little studied. We assess these programs by exploring community participation in, and barriers to, an urban tree distribution program in Fort Lauderdale, United States and the role socioeconomic background and tree functional types have on participation. We use a mixed-methods approach, panel data, choice experiments, and econometrics to quantitatively analyze respondent’s ranking of program options. High income, White respondents had the highest level of awareness and participation while low income, African Americans (AA) had the lowest level. Monetary rebates were perceived as positive and significant as the compensation value increased to US$8.00 - $12.00. Fruit-bearing and native tree functional types were more preferred than flowering or shade trees. Latinos, AA, and high income respondents preferred fruit trees, while White, high income preferred native trees. Overall, low income respondents perceived the greatest barriers towards participation. 20% of Broward County residents who participated in the survey were aware of the tree giveaway programs and 13% had previously participated. Findings indicate an adaptive governance mismatch between program objectives to equitably increase city tree cover via planting shade trees versus individual’s knowledge and preference for other tree types and functions. Results can be used for developing and evaluating reforestation initiatives to equitably increase tree cover and improve the governance of urban ecosystems. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.